ORGANIZATION OF SCIENTIFIC AND RESEARCH PROCESSES BASED ON INFORMATION AND DIGITAL TECHNOLOGIES IN HIGHER EDUCATION - Mamajanov, Shavkatjon; Obidov, Avazbek (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
In this article, the ways of using digital technologies, the stages of their implementation, and the analysis of the results are highlighted. This work recommends what to pay attention to when monitoring and evaluating research, as well as the sequence of organizing and conducting research in higher education.